Light-dependent impact of salinity on the ecophysiology of Synechococcus elongatus PCC 7942: Genetic and comparative protein structure analyses of UV-absorbing mycosporine-like amino acids (MAAs) biosynthesis - Kumar, Vinod; Mondal, Soumila; Gupta, Anjali; Maurya, Pankaj K.; Sinha, Rajeshwar P.; Häder, Donat-Peter; Singh, Shailendra P. (Environmental and Experimental Botany, 2021)
Cyanobacteria are subjected to a dynamic light environment in their natural habitat or artificial cultivation system. The fluctuating light environment is associated with increased salinity stress due to the evaporation of the growth medium. Therefore, it is important to understand the physiology of the organisms under a dynamic environment of light and salinity which together affect the fitness and overall performance of the organism. We studied the growth behavior and other physiological parameters of Synechococcus elongatus PCC 7942 in the presence of different NaCl concentrations (0, 50, 100 and 200 mM) and light conditions such as low PAR (LPAR), high PAR (HPAR) and PAR + UVR using diurnal and continuous photoperiods. We also investigated the ability of S. elongatus PCC 7942 to biosynthesize UV-absorbing mycosporine-like amino acids (MAAs) and conducted genetic and comparative protein structure analyses to better understand its biosynthesis. Results obtained suggest that the impact of salinity stress caused by NaCl on growth behavior and physiological parameters such as photosynthetic pigments, the effective quantum yield of PSII and oxidative stress is dependent on the light environment. These parameters were affected differently by the quality and quantity of light and photoperiods, and the negative effect of salinity was alleviated by a high light environment. S. elongatus PCC 7942 does not biosynthesize MAAs due to the absence of MAAs biosynthesizing genes cluster in its genome. Results from genomic and comparative protein structure analyses suggested that DDGS and DHQS enzymes are different and DDGS but not DHQS is required for MAAs biosynthesis. Understanding the light-dependent impact of salinity stress may help in developing strategies for outdoor cultivation of cyanobacteria for bioenergy and valuable chemicals production by balancing absorbed and utilized radiant energy.
CRIS-Team Scopus Importer:2021-08-27
Keywords: Abiotic stress; Cyanobacteria; DCFH-DA; Photoperiod; Photoprotection; ROS